Impression Management and Employee Contextual Performance in Service Organizations (Enterprises) - Friday Ogbu Edeh; Nurul Mohammad Zayed; Saad Darwish; Vitalii Nitsenko; Iryna Hanechko; K. M. Anwarul Islam (Emerging Science Journal, 2023)
This study aims to investigate the effect of impression management on employee contextual performance in service organizations using quantitative methods. The social influence theory, which explains the role of superior influence over the subordinate, served as the theoretical underpinning for the study. A cross-sectional survey design was adopted in line with positivism research philosophy. The accessible population of this study consists of one hundred selected service-oriented firms (four-star hotels, fast food restaurants, and travel agencies) operating in the southern part of Nigeria. The sample consists of middle managers, human resource managers, front desk officers, housekeepers, and customer relationship managers. Frequency distribution was used to analyze participants’ profiles, while linear regression was employed to analyze the formulated hypotheses. Statistical Package for the Social Sciences (SPSS) 20.0 served as statistical software. Linear regression results suggest that self-promotion exerted a significant positive effect on co-worker support. Ingratiation demonstrated a significant positive effect on customer satisfaction. It appears that exemplification exerted a significant positive effect on enterprise compliance. The outcome of this study has demonstrated that traditional managerial skills can no longer hold water in contemporary service-oriented organizations because of the workplace's dynamic and changing technological structure. This study concludes that impression management can assist managers in influencing their employees positively to achieve organizational objectives. Doi: 10.28991/ESJ-2023-07-02-05 Full Text: PDF